Student Engagement and Achievement with a Digital Literacy E-Module - Haris Nasution; Efendi Napitupulu; Enny Keristiana Sinaga (Academia Open, 2025)
General Background: Digital literacy has become essential for students to navigate, evaluate, and create information in today’s technology-driven learning environments. Specific Background: At MTsN 3 Langkat, class VIII Informatics students traditionally rely on teacher-led instruction, with limited opportunities to independently source and transform information. Knowledge Gap: Despite the proliferation of e-learning tools, little is known about how digital literacy–based e-modules affect both learner motivation and academic performance in middle-school Informatics. Aims: This Classroom Action Research (CAR) investigation examined whether implementing a digital literacy–focused e-module could enhance motivation and learning outcomes among eighth-grade Informatics students in the 2024/2025 academic year. Results: Over successive CAR cycles—comprising planning, implementation, observation, and reflection—students demonstrated notable gains in engagement and achieved higher assessment scores. Novelty: This study uniquely combines e-module design with collaborative knowledge construction through student-driven information sourcing. Implications: Findings suggest that integrating digital literacy frameworks into e-module development can foster deeper learner engagement and improve Informatics achievement in similar educational contexts. Highlights: Emphasizes digital literacy integration through self-guided e-modules. Utilizes cyclical CAR stages (planning, action, observation, reflection). Demonstrates measurable gains in both motivation and academic performance. Keywords: E-Module, Digital Literacy, Classroom Action Research, Student Motivation, Learning Outcomes